SENYAWA AKTIF ANTIMAKANDARI UMBI GADUNG (Dioscorea hispida Dennst) - Rahayu Santi, Sri (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 1 Januari 2010, 2012)
Isolation and identification of active antifeedant compounds from gadung tuber (Dioscorea hispida Dennst) has been carried out. As much as 12.03 g of concentrated methanol extract was resulted from 5.0 kg dry gadung tuber that was macerated using methanol. Further, this extract was partitioned with n-hexane to obtain 2 concentrated extracts in n-hexane and methanol. The result of antifeedant test showed that the methanol extract was more active than the n-hexane extract. Separations of the methanol extract using column chromatography (stationary phase : silica gel 60, mobile phase : methanol-chloroform 6:5) resulted four fractions. The most active fraction, FA , showed 2 spots on the TLC, so it was separated using preparative TLC which resulted in 2 fractions (FA.1 and FA.2). The antifeedant activity of FA.1 fraction was higher than FA.2 fraction and it gave only 1 spot on the TLC The result of identification using phytochemical test and spectrophotometer analysis suggested that FA.1 fraction was alkaloid compound whose maximum wave length was 277.1 nm and it contained N-H (3425.3 cm-1), CH aliphatic (2927.7 and 2854.5 cm-1), C=O (1735.8 cm-1), C-N (1110.9 cm-1) and N-C=O (621.9 cm-1).
Keywords: Dioscorea hispida Dennst., antifeedant, isolation, identification